2002
DOI: 10.1007/s004250100667
|View full text |Cite
|
Sign up to set email alerts
|

Changes in oxidative processes and components of the antioxidant system during tomato fruit ripening

Abstract: Analysis of the oxidative processes taking place during fruit ripening in a salad tomato variety (Lycopersicon esculentum Mill. cv. Ailsa Craig) revealed changes in oxidative and antioxidative parameters. Hydrogen peroxide content, lipid peroxidation and protein oxidation were measured as indices of oxidative processes and all were found to increase at the breaker stage. The levels of the aqueous-phase antioxidants, glutathione and ascorbate, increased during the ripening process and these increases were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
308
8
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(361 citation statements)
references
References 57 publications
(64 reference statements)
37
308
8
8
Order By: Relevance
“…5e). Jiménez et al (2002) was reported that MDHAR transcript correlated well with MDHAR activity; whereas, in our study we did not find a correlation between MDHAR activity and SlMDHAR transcript accumulation under water stress, suggested a post-transcription regulation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…5e). Jiménez et al (2002) was reported that MDHAR transcript correlated well with MDHAR activity; whereas, in our study we did not find a correlation between MDHAR activity and SlMDHAR transcript accumulation under water stress, suggested a post-transcription regulation.…”
Section: Discussioncontrasting
confidence: 99%
“…These results agree with our previous results, where water stress caused changes in AsA and DHA concentrations in tomato fruits (Murshed et al 2008a). These changes in AsA and DHA concentrations in fruits under water stress treatments would occur because of either changes in AsA synthesis or changes in AsA regeneration from DHA, which can result from water stress-induced changes in MDHAR and DHAR activities (Jiménez et al 2002). Given that ascorbate can directly scavenge superoxide, hydroxyl radicals and singlet oxygen and reduce H 2 O 2 to water via the APX reaction (Noctor and Foyer 1998), the increase of AsA concentration in tomato plants suggests an important role for this antioxidant against oxidative stress provoked by water stress.…”
Section: Discussionmentioning
confidence: 99%
“…We measured the activity of CAT, SOD, APX, and GR in the pericarp of fruits at different ripening stages. Previous data had been reported about fruit antioxidant enzymes in other tomato varieties, but when the fruit ripened on the plant (Jiménez et al 2002a). This is the first time that the antioxidant system is analyzed in tomato fruits during postharvest ripening after conservation at low, non-freezing temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…During the life cycle, plants overcome genetically regulated processes that lead to the production of ROS such as senescence (Kukavica and Jovanovic 2004) and ripening. Ripening, described as an oxidative process (Brennan and Frenkel 1977, Jiménez et al 2002a, Jiménez et al 2002b, Rogiers et al 1998, is accompanied by changes in flavor, texture, color, and aroma. Climacteric fruits such as tomato also show a burst of ethylene biosynthesis and an increase in respiration during ripening (White 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in vitamin C content of mango fruit with ripening may be due to physiological activities that persist after harvesting of the fruit, which is the breakdown of starch to glucose, and this causes an increase in the biosynthesis of ascorbic acid. The increase in ascorbic acid content during ripening has also been attributed to the increase in lipid peroxidation which is another physiological activity going on in the ripened fruit (Jimenez et al, 2002). The total phenolic content of the mango peel was determined and reported as mg gallic acid equivalent (GAE) per g sample as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%